(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Tribal women, just as other social groups, form half of their entire population. Tribal societies usually consider the gender to be civil and free in which all the roles are described but are civil to one another. Men emphasize agriculture while women are in plantation and collect foods which would mean that both the roles are important and complement each other in relation of their society. This paper highlights the issues of tribal women in present scenario and how the minor forest product changes the life of tribal women in India. This paper is based on secondary data and ethnographic method.